Perceptions of Barriers to and Facilitators of Participation in Health Research Among Transgender People - Owen-Smith, Ashli A. (Transgend Health, 2016)
Purpose: Although transgender people may be at increased risk for a range of health problems, they have been the subject of relatively little health research. An important step toward expanding the evidence base is to understand and address the reasons for nonparticipation and dropout. The aim of this study was to explore the perceptions of barriers to and facilitators of participation in health research among a sample of transgender people in San Francisco, CA, and Atlanta, GA. Methods: Twelve in-person focus groups (FGs) were conducted; six (three with transwomen, three with transmen) were conducted in San Francisco and six FGs were conducted in Atlanta (three with transwomen and three with transmen). FGs were audiorecorded, transcribed, and uploaded to MaxQDA software for analysis. A codebook was used to code transcripts; new codes were added iteratively as they arose. All transcripts were coded by at least 2 of the 4 researchers and, after each transcript was coded, the researchers met to discuss any discrepancies, which were resolved by consensus. Results: Among 67 FG participants, 37 (55%) identified as transmen and 30 (45%) identified as transwomen. The average age of participants was ∼41 years (range 18–67) and the majority (61%) were non-Hispanic Whites. Several barriers that can hinder participation in health research were identified, including logistical concerns, issues related to mistrust, a lack of awareness about participation opportunities, and psychosocial/emotional concerns related to being “outed.” A broad range of facilitators were also identified, including the opportunity to gain knowledge, access medical services, and contribute to the transgender community. Conclusion: These findings provide insights about the perceived barriers to and facilitators of research participation and offer some guidance for researchers in our ongoing effort to engage the transgender community in health research.